Performance Development Models Based on The Concept of Coersive Digital Leadership: The Role of Curiosity As A Manifestation of Intrinsic Motivation - Ratih Pratiwi; Aprih Santoso; Windi NR Wardhani; Marno Nugroho (Business Review and Case Studies, 2022)
The goal of this study was to examine the performance development model used by lecturers at private Islamic universities in Central Java, which was based on the idea of coercive digital leadership supported by a trait of intrinsic motivation called curiosity. The population in this study was the head of the undergraduate study program of Private Islamic Universities in Central Java in the form of a university institution. The sampling method using purposive sampling technique was 80 Head of Undergraduate Study Programs at Private Islamic Universities in Central Java who hold the position of Head of Study Programs at Islamic University in Central Java. Data analysis in this study used Partial Least Square (PLS). According to study utilizing PLS analysis, curiosity significantly improves performance and had a good impact on coercive digital leadership. The performance of lecturers was significantly improved through coercive digital leadership. So that the model for improving Lecturer performance can be carried out by implementing Coercive digital leadership which was triggered by increasing Lecturer curiosity. Keywords: curiosity, leadership, lecturer, performance, universities